Parentalidade homoafetiva: um estudo sócio-jurídico sobre o direito de casais homoafetivos procriarem por meio de tecnologias reprodutivas - CARNEIRO, Thiago Lima (Universidade Federal do Pará, 2019)
In this master's thesis, the issue of discrimination against the homosexual subject is discussed through the relation between homosexuality, parenting and assisted reproduction. It seeks to analyze to what extent the parental rights of the homosexual person are vilified by social practice and state powers. For this, the work is divided into three chapters: the first deals with the role of the State in the construction and reproduction of a heterosexist social reality, and how this dominant logic, based on a system of oppositions, is decisive for the subjection of individuals who do not follow the hegemonic sexual order. The perpetuation of this rationality unfolds in discriminations and social marginalizations that prevent the homosexual person from exercising his rights equally to other citizens. Only in the last years has been seen a more egalitarian treatment in relation to these individuals in Brazil, with the recognition of some rights claimed, such as the possibility of contracting marriage. The purpose of the second chapter is to evaluate the current family situation protected by the Brazilian legal system and to examine the framework given by the decision of the Federal Supreme Court to recognize the homoaffective union as a family entity. The third and final chapter deals with homoaffective parenting in the context of assisted reproduction, with emphasis on the specificities of this scenario, legal protection and access to reproductive technologies. The research and development of the dissertation was based on the doctrinal construction related to the subject, based on relevant scientific books and articles, documental analysis and semi-structured interviews directed to professionals working in the area of human reproduction. Finally, it is concluded that the validity of a heterosexist hegemonic order has a substantial impact on the enjoyment of the parental rights of the homosexual person, either by discriminating against the family dynamics or by compelling them to submit to the dominant living standards, interfering with their freedom of exercising parenthood.